A Study of Chemical Compound of Graph with help of Computer Coding (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this research work we study about the outline of graph structures algorithms required for the recognition of chemical graphs by a computer automatic encoding of organic chemical structures into the line formula notation. During the study we will first classify chemical graph then find a planar projection and fundamental cycles of a chemical graph with its characterization. Then we draw that for automatic construction code from the connection table for this we need some algorithms. Thus a graph structure language like GRAAL should prove useful for chemical coding systems. Further development along these lines should be helpful in coding knotted chemical structures.